Community lawyering and climate justice: A new frontier. (September 2022) - Taylor, Monica; Lay, Bronwyn
Climate change threatens the livelihoods of poor and marginalised people as they have the least capacity to adapt, recover and respond to climate events. This article presents climate justice as a new frontier for the Australian community legal sector and puts forward three key reasons why community legal centres (CLCs) are ideally suited to the challenge of climate justice-related legal work.